Efektivitas Pelatihan Regulasi Emosi Terhadap Penurunan Kecemasan Ibu Hamil di Puskesmas X - Imroatu Sholikhati Setyo; Suroso Suroso (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
ABSTRACT The study purpose was to examine the effectiveness of emotion regulation training in reducing anxiety among pregnant women at Puskesmas X, Surabaya, and to promote maternal mental health through community-based psychological services. This intervention was designed as part of a preventive and promotive effort within primary healthcare to identify and manage emotional challenges experienced during pregnancy. Materials and methods. The study employed a mixed-method approach combining qualitative and quantitative data collection through interviews, observations, and psychological screening using the Depression, Anxiety, and Stress Scale (DASS). Participants consisted of ten pregnant women aged 25–38 years who were identified as having moderate levels of anxiety. The intervention was conducted through two group sessions of emotion regulation training consisting of five core components: recognizing emotions, expressing emotions, managing emotions, transforming negative emotions into positive ones, and relaxation techniques. Data were analyzed using paired-sample comparisons to evaluate pre–post intervention differences. Results. The findings showed a noticeable decrease in anxiety levels after the training sessions. Participants demonstrated improved understanding of emotional awareness, reduced physiological symptoms (such as tension and restlessness), and better control of their thoughts and behaviors. Conclusions. Emotion regulation training effectively reduced prenatal anxiety among participants and enhanced their emotional well-being. Integrating psychoeducation, family participation, and collaboration with healthcare workers is recommended to support sustainable maternal mental health care in primary health settings. Keywords: Prenatal anxiety, emotion regulation, psychoeducation, maternal mental health, community intervention